The ability of flower farmers in Da Lat to meet the needs of downstream buyers - Le, B.; Batt, Peter (2013)
The purpose of this study is to explore the gaps between what cut flower growers in Da Lat, Viet Nam, were able to deliver to their downstream customers and what their downstream customers actually wanted. Identifying and rectifying these gaps offers a means of improving the performance of the supply chain and of offering superior value to all actors in the value chain. In this study, 206 farmers, 41 traders, 41 wholesalers and 42 retailers in Da Lat were interviewed. Results suggest that farmers need to improve the quality of the cut flowers offered for sale and their ability to deliver in sufficient quantities when required.